Apgar Scores and Long-Term Risk of Epilepsy - Yuelian Sun; Mogens Vestergaard; Carsten Bøcker Pedersen; Jakob Christensen; Jørn Olsen (2006)
Background: Low Apgar scores are associated with high risk of neonatal death, cerebral palsy, and mental retardation, but the association between Apgar scores and long-term risk of epilepsy remains unresolved. Methods: We carried out a population-based cohort study of 1,538,732 live newborns in Denmark between 1 January 1978 and 31 December 2002 by using national registers. The Apgar scores at 1 or 5 minutes were recorded by midwives following standardized procedures. We obtained information on epilepsy by linking the cohort with the National Hospital Register. Cohort members were followed from birth until onset of epilepsy, death, emigration, or 31 December 2002, whichever came first. Results: The incidence rate of epilepsy increased consistently with decreasing Apgar scores. The incidence rate of epilepsy was 628 per 100,000 person-years for those with 5-minute Apgar scores of 1 to 3 and 86 per 100,000 person-years for those with a score of 10; the resulting incidence rate ratio was 7.1 (95% confidence interval = 5.8–8.8). The incidence rate ratios of epilepsy associated with low Apgar scores were particularly high in early childhood but remained high into adulthood. The association did not change after excluding children with cerebral palsy, congenital malformations, or a parental history of epilepsy. Conclusions: Neonates with a suboptimal Apgar score have a higher risk of epilepsy that lasts into adult life. These findings suggest that prenatal or perinatal factors play a larger role in the etiology of epilepsy than has previously been recognized.